2019
DOI: 10.3892/ol.2019.10259
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic melanoma: Demographic and clinicopathological features and disease‑specific prognostic factors

Abstract: Desmoplastic melanoma (DM) is a rare morphological subtype of melanoma that remains uncharacterized. The aim of the present study was to investigate the incidence of DM, its general demographics, clinicopathological features and disease-specific prognostic factors. DM cases were sampled from the Surveillance, Epidemiology and End Results (SEER) program from between 1973 and 2017. A total of 3,657 cases (median age, 68 years) were identified. The results indicated that DM primarily occurred in Caucasian subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Therefore, the level of invasion was not enabled into the present study. Additionally, the choice of surgery treatment could improve OS and was a vital protective factor in patients with NMMM, which was consistent with previous research 24 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, the level of invasion was not enabled into the present study. Additionally, the choice of surgery treatment could improve OS and was a vital protective factor in patients with NMMM, which was consistent with previous research 24 …”
Section: Discussionsupporting
confidence: 90%
“…Additionally, the choice of surgery treatment could improve OS and was a vital protective factor in patients with NMMM, which was consistent with previous research. 24 Yang et al developed and validated a nomogram for predicting the risk of a cutaneous histopathological subtype of nodular melanoma, and the nomogram was constructed by incorporating several common related factors, including age at diagnosis, sex, marital status, AJCC stage, SEER stage, and lymph node density. 15 But in our manuscript, we selected common independent risk factors in patients with NMMM as follows: age, sex, race, marital status, anatomic site, stage, depth ulceration, mitoses, and treatment, and these factors were more readily available and comprehensive in clinical work.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Surgery resection is the most widely used treatment, and has also been identified as an independent prognostic factor of DM in terms of overall survival. 40 During resection surgery, the resection is determined by tumor invasion depth. Studies revealed that although the presence of neurophilic features could not predict the survival rate in DM, it did correlate with a higher recurrence rate.…”
Section: Diagnosismentioning
confidence: 99%
“…Desmoplastic melanoma often has ill-defined clinical margins and occurs most commonly on the head and neck in older patients. 1–6 Subtle spindle-shaped or neurotropic melanocytes may not be detected with routine hematoxylin and eosin stains. 7–11…”
mentioning
confidence: 99%